2022
DOI: 10.1126/scisignal.abq5389
|View full text |Cite
|
Sign up to set email alerts
|

Stress signaling boosts interferon-induced gene transcription in macrophages

Abstract: Promoters of antimicrobial genes function as logic boards, integrating signals of innate immune responses. One such set of genes is stimulated by interferon (IFN) signaling, and the expression of these genes [IFN-stimulated genes (ISGs)] can be further modulated by cell stress–induced pathways. Here, we investigated the global effect of stress-induced p38 mitogen-activated protein kinase (MAPK) signaling on the response of macrophages to IFN. In response to cell stress that coincided with IFN exposure, the p38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…These discrepancies can be reconciled by the evidence that both ERα and ERβ activate discordant signaling pathways in all cell lines, including neurons. In fact, the binding of PPT or E2 to ERα triggers the persistent activation of the PI3K/AKT and ERK/MAPK signaling pathways, which inhibit the activation of the p38 pathway that is activated by the binding of E2 or DPN to ERβ [ 6 , 23 , 50 , 51 , 52 ]. While PPT and DPN activate one or the other pathway, E2, by binding both receptor subtypes, leads to a balance between the divergent signal pathways activated by the two receptor subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These discrepancies can be reconciled by the evidence that both ERα and ERβ activate discordant signaling pathways in all cell lines, including neurons. In fact, the binding of PPT or E2 to ERα triggers the persistent activation of the PI3K/AKT and ERK/MAPK signaling pathways, which inhibit the activation of the p38 pathway that is activated by the binding of E2 or DPN to ERβ [ 6 , 23 , 50 , 51 , 52 ]. While PPT and DPN activate one or the other pathway, E2, by binding both receptor subtypes, leads to a balance between the divergent signal pathways activated by the two receptor subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that cycloheximide alters protein degradation through activation of protein kinase B (PKB/AKT) [ 51 ], further enhancing NGB levels. On the other hand, resveratrol triggers the p38 activation, a well-known inducer of several transcription factors including CREB activation [ 52 , 53 , 54 ] that could overcome NRSF inhibition allowing Ngb transcription. Although Res stimulation prevents NGB degradation and enhances Ngb transcription, the contemporary treatment with cycloheximide reduces the NGB translation and the NGB protein overexpression could not occur.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, both p38 and JNK kinases have been implicated in the host antiviral response (Faist et al, 2023; Mikkelsen et al, 2009; Wang et al, 2019). Conversely, excessive activation of p38 can lead to cytokine storm and tissue damage (Boccuni et al, 2022; Faist et al, 2023) and pharmacological inhibition of p38 has been shown to suppress the expression of pro-inflammatory cytokines, including IFN-β, in cells infected with SARS-CoV-2 (Faist et al, 2023). Thus, it is plausible that under resting conditions, the RBP/GIGYF1/eIF3 axis maintains mRNAs that encode the pro-inflammatory cytokines such as IFN-β in a translationally repressed state.…”
Section: Discussionmentioning
confidence: 99%
“…The combined impact of TgIST, GRA28, GRA16, and GRA24 prompts the question of their individual roles in the complex process of modulating the host’s IFNγ response. p38 MAPK was shown to be directly involved in IFNγ signaling and in the transcriptional activation of ISGs via the GAS promoter elements (6870). GRA24 has been shown to activate proinflammatory genes, including multiple (i.e., STAT1, IL12B, NOS2) within the IFNγ signaling pathway (53).…”
Section: Discussionmentioning
confidence: 99%